IMPLEMENTASI PENGELOLAAN DANA DESA (Studi Kasus: Tantangan dan Hambatan Dalam Pengelolaan Dana Desa Di Desa Ria Bao, Kecamatan Nagawutung, Kabupaten Lembata) - Simbolon, Gallex; Lewowerang, Yosef Raimondo (Universitas Nusa Cendana, 2022)
ABSTRACT The results of the analysis show that the implementation of village funds includes communication, resources, both natural and human resources, commitment and bureaucracy. The roles and responsibilities of the village government, village officials and the community in managing village funds are based on budgeted mechanisms and programs. The challenges and obstacles faced in managing village funds both externallyand internally. External challenges are in the form of regulatory changes that make it difficult to prepare documents. Internal challenges are more directed to the readiness of therequired documents to carry out the process of disbursing and realizing the budget. There are also obstacles faced, namely internally related to regulations or regulations that often become obstacles in the process of disbursing village funds. Externally, namely the difficulties encountered related to the process of disbursement or realization to the target recipients of the budget. In addition, there is also an evaluation process for managing village funds, which consists of an evaluation process, coordination and consultation mechanisms, roles in the village as community members, knowledge of village funds and village fund management.T he suggestions that can be given are the need to increase competence through internal socialization to each stakeholder who has an interest in managing village funds, the need to revise the mechanism and flow of village fund management at the village level so that budget realization reaps community satisfaction as a target and the need for transparency regarding the evaluation of the use of village funds. Keywords: Implementation, Management, Program, Budget Realization.